Formação de professores alfabetizadores em contexto de HTPC - Simões, Lucy Conceição (2009)
This work focuses the education of Literacy Teachers , in HTPC (meetings for teacher education) context, under the critical reflexive perspective. The objectives of this research are to investigate what themes are tackled by Literacy teachers on their discourses about their practices, and to analyze how the formative-researcher contributes to these teachers development. The context of the research is a state public school located in the East side of São Paulo. Fifteen teachers, the principal, the vice-principal, the pedagogical coordinator and the formative-researcher took part in this research. This is a criticalcollaborative research (Magalhães, 1994a, 1998, 2007), in which language is taken as place of negotiation and reflection to analyze teachers choices (Liberali, 2004). Considering the description, discussion and explanation of the concepts which are observed on teachers actions, their pertinence and relevance are evaluated in order to understand the educator s role in a determined socio-historic-cultural context (Vygotsky, 1934/1991, 1930-33/2007). The thematic contents (Bronckart, 2007) and the interaction of six HTPC meetings are analyzed (Kerbrat-Orecchioni, 1943/2003) to make sure what themes are predominant through these discussions and also to observe if the formative-researcher is able to promote the realm to these themes resignification (Vygotsky, 1934/2000). Data shows that the researcher seems to have established grounds for critical reflection, as a formative one. There are evidences that she has been changing her actions, while she analyzes and confront them to the theories that support the language of critical reflection